Pharmacodynamics, Efficacy, and Safety of IPX203 in Parkinson Disease Patients With Motor Fluctuations. Issue 5 (September 2019) - Modi, Nishit B.; Mittur, Aravind; Dinh, Phillip; Rubens, Robert; Gupta, Suneel
Abstract : Objectives: IPX203 is an investigational oral extended-release capsule formulation of carbidopa and levodopa. The pharmacodynamics and efficacy of IPX203 were compared with immediate-release carbidopa-levodopa (IR CD-LD) in this open-label, rater-blinded, multicenter, crossover study in patients with advanced Parkinson disease (PD). Methods: Twenty-eight patients were randomized to 2 weeks of treatment with IR CD-LD followed by IPX203 or IPX203 followed by IR CD-LD. Pharmacokinetic and motor assessments were conducted on days 1 and 15 of each treatment period. Efficacy was assessed using a 3-day PD diary. Pharmacodynamics were assessed by rater-blinded Movement Disorder Society—Unified Parkinson's Disease Rating Scale Part III and Investigator Assessment of Subject's Motor State. Results: After a single dose, levodopa concentrations were sustained above 50% of peak concentration for 4.6 hours with IPX203 versus 1.5 hours with IR CD-LD ( P < 0.0001). Based on the PD diary, patients experienced significantly less Off time with IPX203 as a percentage of waking hours than IR CD-LD (mean 19.3% vs 33.5%, respectively; P < 0.0001), translating into 2.3 hours less Off time than IR CD-LD with most of this improvement (1.9 hours) being Good On time. There was no significant difference in the amount of On time with troublesome dyskinesia between treatments. Pharmacodynamic assessments demonstrated similar outcomes in favor of IPX203 on day 1 and a significant predose benefit on motor examination after multiple dosing. Conclusions: IPX203 demonstrated a sustained effect to reduce Off time and improve Good On time in patients with PD and motor fluctuations. Both treatments were well tolerated.